FRI0388 SECUKINUMAB IMPROVES HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH ANKYLOSING SPONDYLITIS, IRRESPECTIVE OF TIME SINCE FIRST DIAGNOSIS: POOLED RESULTS FROM THE SECUKINUMAB PHASE 3 TRIAL PROGRAM. (June 2019) - Deodhar, Atul; Boonen, Annelies; Ferraccioli, Gianfranco; Bosch, Filip van den; Martinez, David; Porter, Brian; Shete, Abhijit; Gilloteau, Isabelle; Yocolly, Aurore; Strand, Vibeke
Abstract : Background: Ankylosing spondylitis (AS) is a chronic rheumatic condition that has a negative impact on health-related quality of life (HRQoL). Secukinumab (SEC), a fully human anti-IL-17A monoclonal antibody, has been shown to effectively control AS symptoms and improve HRQoL. Objectives: To evaluate the impact of SEC on HRQoL, assessed by the Short Form-36 Health Survey (SF-36), in pts with active AS stratified by time since first diagnosis (<2 or ≥2 yrs). Methods: Pts were randomized to placebo (PBO) or SEC in MEASURE 1 (10 mg/kg intravenously followed by 150 or 75 mg SC), MEASURE 2 (150 or 75 mg SC) and MEASURE 4 (150 mg SC with/without SC loading). At Wk 16 or Wk 24, depending on ASAS 20 response, pts on PBO were re-randomized to SEC. Mixed-models for repeated measures were used to evaluate changes in SF-36 from baseline (BL) to Wk 16; observed data are presented at Wk 52. The proportion of pts reporting improvements meeting/exceeding the minimal clinically important differences (MCID) for SF-36 physical (PCS responders) and mental component summary (MCS responders), and individual SF-36 domains was also assessed. Missing data were recorded as non-response and Fisher's exact test was used to compare the proportion of responders between groups at Wk 16. Only pooled data for pts receiving the licensed dose of SEC (150 mg) are shown. Results: Overall 739 patients were included, with 427 and 312 in the SEC 150 mg and PBO groups, respectively. Of those, 37% and 36% of the SEC and PBO groups, respectively, were classified as <2 yrs since first AS diagnosis (Overall: 37%). The mean time since AS diagnosis was similar for the PBO and SEC treatment groups in both the <2 yrs (approx. 0.80 yrs) and the ≥2 yrs subgroups (approx.11 yrs). The least squares mean (LSM) changes in PCS from BL to Wk 16 were increased with SEC 150 mg compared with PBO, in both <2 yrs (PBO: 2.11; 150 mg: 6.44, p<0.0001) and ≥2 yrs since diagnosis (PBO: 3.03; 150 mg: 5.82, p<0.0001) groups. Significant increases were also reported in LSM changes in MCS scores from BL to Wk 16 with SEC 150 mg in patients <2 yrs since diagnosis (PBO: 2.10; 150 mg: 5.53, p<0.01), but not in the ≥2 yrs group. Analysis of individual SF-36 domain scores showed improvements with SEC vs PBO in the overall population and in both time since diagnosis subgroups, except Role-Emotional and Mental Health in the ≥2 yrs group (Figure). At Wk 16, the proportions of PCS responders were significantly higher with SEC 150 mg vs PBO, regardless of time since diagnosis (<2 yrs: PBO = 50.0%, SEC = 73.6%, p<0.01; ≥2 yrs: PBO = 45.0%, SEC = 69.8%, p<0.0001). MCS responses were not significantly different with SEC vs PBO in either subgroup. Overall, improvements in SF-36 scores and clinically meaningful MCID responses with SEC were more prominent in the <2 yrs since diagnosis compared with the ≥2 yrs group. Improvements in PCS, MCS, individual SF-36 domains and overall MCID responses were sustained to Wk 52 with SEC 150 mg. Conclusion: Treatment with SEC 150 mg resulted in significant, clinically meaningful, and sustained improvements in HRQoL. Although reported irrespective of time since AS diagnosis, improvements were more prominent in earlier diagnosed pts. Acknowledgement: Study sponsored by Novartis. Medical writing support by Seren Communications, funded by Novartis. Disclosure of Interests: Atul Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Eli Lilly, Janssen, Novartis, Pfizer, and UCB, Annelies Boonen: None declared, Gianfranco Ferraccioli Speakers bureau: LILLY, ROCHE, NOVARTIS, Filip van den Bosch Consultant for: AbbVie, BMS, Galapagos, Janssen, Lilly, Merck, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, BMS, Janssen, Lilly, Merck, Novartis, Pfizer and UCB., David Martinez Consultant for: I developed the analyses of this study paid by the pharmaceutical., Brian Porter Shareholder of: Novartis, Employee of: Novartis, Abhijit Shete Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG, Isabelle Gilloteau Employee of: Employee of Novartis, Aurore Yocolly Employee of: Employee of Novartis, Vibeke Strand Consultant for: Samumed, LLC, AbbVie, Amgen, EMD Serono, Eupraxia, Flexion, Iroko, Novartis, Pfizer, Regeneron, Sanofi, SKK